Evaluation of facies heterogeneity in reef carbonate reservoirs: A case study from the oil field, Perm Krai, Central-Eastern Russia; Geoenergy Science and Engineering; Vol. 227 - Martyushev D. A. Dmitry Aleksandrovich; Chalova P. O. Polina; Davoodi Sh. Shadfar; Ashraf U. Umar (2023, 2023)
Title screen